Eksplorasi Parasit pada Ikan Nila (Oreochromis niloticus) dari Penjual Ikan Lokal di Dramaga, Bogor - Azizah, Hanifah Nur; Nugraha, Arifin Budiman; Juniantito, Vetnizah; Cahyaningsih, Umi (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2022)
The demand for tilapia fishing goods has recently expanded on a national scale. One of the difficulties this fish farming operation encountered was the parasite-caused illness. The aims of this study were to explore parasites in tilapia (Oreochromis niloticus) from the local fish seller in Dramaga, Bogor, West Java. A total of 14 tilapia were sampled, with an average length of 22 cm and a body weight of 195 grams. Fish gills, pectoral fins, caudal fins, tail fins, dorsal fins, scales, and intestines were collected. The methods used in this study were wet mount examination, gut samples stained with Ziehl Neelsen, and blood samples from fish obtained and stained with Giemsa for analysis. The findings revealed that Trichodina sp. (85.71 percent) was present in several organs, with the gills being the most heavily affected organ. The intensity of this parasite was 27.83 individuals/head. The parasites detected by Ziehl Neelsen staining were Myxobolus sp. (57.14 %), Cryptosporidium spp. (35.71 %), and Cyclospora sp. (14.29%). The type of blood parasite found was identified as Hemogregarina sp (50%). Our findings are very important information for initiating the development of a treatment strategy to prevent parasite infection in tilapia fish farms.